Plug in the values of p and q where you see them in the equation:
-(2+4)2 / (-6) - Distribute the -1
(-2-4)2 / (-6) - Distribute the 2
(-4-8) / (-6) - Subtract what's inside the parenthesis
(-12) / (-6) - Divide
The answer is 2
Answer:
No conozco esta respuesta. Esta en el libro
Step-by-step explanation:
A because everything after the verb is a preposition
<span> f(x)=4x^8+7x^7+1x^6+
</span>∴<span> f(-2)=4(-2)^8+7(-2)^7+1(-2)^6+1
</span>∴ <span>f(-2)=(4x256) + (7x-128) + (1x64) +1
</span>∴ <span>f(-2)=1024 - 896 + 64 +1
</span>∴ <span>f(-2)= 193</span>
Answer
Movie -Enola Holmes
Show- Brooklyn 99 and The Superstore
Step-by-step explanation: